The Criminal Jury, Moral Judgments, and Political Representation - Lee, Youngjae (2018)
Was the sexual act consensual? Did the defendant have a reasonable belief that he was in imminent danger of death by an attacker? Did the police use excessive force? Did the defendant act in a heinous or cruel manner? Did the defendant act with depraved indifference to human life? These are some of the questions that criminal juries encounter. Determinations of such questions involve a combination of factual and moral questions, both questions about what happened and questions about the evaluative significance of what happened. This feature of the criminal jury—that the jury routinely decides normative questions—is frequently noted but is rarely examined. What does it exactly mean when we say that juries make normative determinations, and what is the nature of the inquiry that the jurors are engaging in when they consider moral questions in this particular setting? More specifically, this Article asks whether a juror, when making moral judgments, should follow his or her individual moral beliefs or identify and implement the community’s perspective. Many things said about the criminal jury appear to support the view that the jurors should attempt to replicate the community’s perspective. It is often said, for instance, the criminal jury serves as the community’s conscience, representative, or fiduciary, and such formulations suggest an obligation on the part of the jurors to reproduce the community’s perspective. This Article argues that despite the popularity of such accounts, they are either too indeterminate to imply an obligation on the part of the jurors to reproduce the community’s perspective, or in conflict with the fundamental obligation of jurors to adjudicate fairly and accurately. This Article, therefore, concludes that we are better off jettisoning the talk of the criminal jury as the community’s conscience, representative, or fiduciary, at least in this context, and should instead embrace the notion that jurors fulfill their roles in the criminal justice system most effectively when they vote as individuals, not as representatives, by applying legal standards to particular situations and bringing a diversity of viewpoints to the task